Coulometric sodium chloride removal system with Nafion membrane for seawater sample treatment - Grygolowicz-Pawlak, E.; Sohail, M.; Pawlak, M.; Neel, B.; Shvarev, A.; De Marco, Roland; Bakker, E. (American Chemical Society, 2012)
Seawater analysis is one of the most challenging in the field of environmental monitoring, mainly due to disparate concentration levels between the analyte and the salt matrix causing interferences in a variety of analytical techniques. We propose here a miniature electrochemical sample pretreatment system for a rapid removal of NaCl utilizing the coaxial arrangement of an electrode and a tubular Nafion membrane. Upon electrolysis, chloride is deposited at the Ag electrode as AgCl and the sodium counterions are transported across the membrane. This cell was found to work efficiently at potentials higher than 400 mV in both stationary and flow injection mode. Substantial residual currents observed during electrolysis were found to be a result of NaCl back diffusion from the outer side of the membrane due to insufficient permselectivity of the Nafion membrane. It was demonstrated that the residual current can be significantly reduced by adjusting the concentration of the outer solution. On the basis of ion chromatography results, it was found that the designed cell used in flow injection electrolysis mode reduced the NaCl concentration from 0.6 M to 3 mM. This attempt is very important in view of nutrient analysis in seawater where NaCl is a major interfering agent. We demonstrate that the pretreatment of artificial seawater samples does not reduce the content of nitrite or nitrate ions upon electrolysis. A simple diffusion/extraction steady state model is proposed for the optimization of the electrolysis cell characteristics.